2017
DOI: 10.1242/jeb.164061
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of chisel-tooth digging by African mole-rats

Abstract: Mole-rats are known to use their protruding, chisel-like incisors to dig underground networks of tunnels, but it remains unknown how these incisors are used to break and displace the soil. Theoretically, different excavation strategies can be used. Mole-rats could either use their head depressor muscles to power scooping motions of the upper incisors (by nose-down head rotations) or the lower incisors (by nose-up head rotations), or their jaw adductors to grab and break the soil after penetrating both sets of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…Chisel‐tooth diggers have clearly evolved enlarged upper and lower incisors. This result adds to the evidence that chisel‐tooth digging rodents use both their upper and lower incisors, operated by their enlarged masticatory, neck and back muscles, to dig (Van Wassenbergh et al, ).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Chisel‐tooth diggers have clearly evolved enlarged upper and lower incisors. This result adds to the evidence that chisel‐tooth digging rodents use both their upper and lower incisors, operated by their enlarged masticatory, neck and back muscles, to dig (Van Wassenbergh et al, ).…”
Section: Discussionsupporting
confidence: 62%
“…Lower incisor procumbency, unlike that of the upper incisors, does not correlate with digging method within subterranean rodents (Landry, ; Stein, ), which could lead to the assumption that chisel‐tooth digging rodents dig with their more procumbent upper incisors. However, a recent in vivo kinematic study of the chisel‐tooth digging mole‐rat Fukomys micklemi showed that, in fact, both the upper and lower incisors are used in concert with both jaw adductor and head depressor muscles (Van Wassenbergh, Heindryckx, & Adriaens, ). Assuming all chisel‐tooth diggers use both their upper and lower incisors to dig, we can hypothesise that the lower incisors of chisel‐tooth diggers have adapted to dig in a similar manner to the upper incisors.…”
Section: Introductionmentioning
confidence: 99%
“…Frequently, a single apparatus performs multiple functions. In some rodents, such as subterranean mole-rats, the biological role of the jaw apparatus is then to feed, to fight and to dig protective tunnels [38,39].…”
Section: Lost In Translationmentioning
confidence: 99%
“…; Becerra, ; Van Wassenbergh et al. ) and during territory defense and aggressive encounters between males (Vassallo & Busch, ; Zenuto et al. ; Becerra et al.…”
Section: Introductionmentioning
confidence: 99%
“…Cranial anatomy and bite forces vary greatly among species due to differences in diet (e.g. Samuels, 2009) and the engagement of incisors in other behaviors and functions, such as digging (Van Daele et al 2009;Becerra et al 2011;Becerra, 2015;Van Wassenbergh et al 2017) and during territory defense and aggressive encounters between males (Vassallo & Busch, 1992;Zenuto et al 2002;Becerra et al 2012a).…”
Section: Introductionmentioning
confidence: 99%